ENGAGING EXTENSIVE READING PRACTICE MEDIATED BY LET’S READ ASIA IN ONLINE CLASSROOM - Dwi Prihartono (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This research aims to find out the process of students’ engagement during extensive reading practice mediated by Let’s Read Asia and students’ responses during extensive reading practice mediated by Let’s Read Asia at the eleventh grade in one of the Senior High School at Karawang. This research used the qualitative approach and a basic interpretive research as the research design. The data were collected by observation checklist based on guidelines from the Extensive Reading Foundation, online interview by using Whatsapp application, online documentation, and written artifact of students. This research included 4 participants of eleventh grade of senior high school. The result of this research showed that the teacher can engage students, it because students actively followed teacher instructions during the process of extensive reading practice that mediated by Let’s Read Asia. During the extensive reading practice that mediated by Let’s Read Asia students could make their interest to read with books that have self selected by students. The students also give the positive responses in the process of extensive reading practice that mediated by Let’s Read Asia as a media of students reading activity.